Determination of the type of arched carbon fiber reinforced fastening of the preparatory opening for the conditions of the «Dniprovska» mine in weakly metamorphized rocks - Tsivka, Yevhenii (Technology audit and production reserves, 2024)
The object of study is an arched carbon fiber-reinforced support of constant cross-section in a layered massif of weakly metamorphosed rocks. The article presents an analysis of the possible use of arched fiber-reinforced support of constant cross-section in a layered massif of weakly metamorphosed rocks for the conditions of the «Dniprovska» mine (Ukraine) around the preparatory opening. An analysis of the stability of mine openings in Western Donbas mines has shown that it is necessary to modernize the support system by introducing carbon fiber. The main reason for the low stability of the opening is the insufficient load-bearing capacity of the support, while its technical characteristics do not take into account the complex mining and geological conditions. The increase in stresses at mining depth is associated with impact safety, which is a serious problem during mining. Metal arch supports are deformable and have high rock loads and require a high level of energy absorption, i. e., to be very strong and flexible to withstand significant loads and avoid large displacements of the opening walls. Carbon fiber-reinforced plastic is able to ensure the stability of the fastening system and eliminate the existing disadvantages of typical metal arch fasteners, namely, high labour intensity, low production speed and high weight of the structure. In this article, the stress-strain state for the specified conditions and the carbon fiber-reinforced plastic arch support of constant cross-section was analyzed using the SolidWorks software product, taking into account the physical and mechanical properties of carbon fiber-reinforced plastic and layered rocks. Taking into account the results of laboratory tests of an equivalent layered array on a press made of PLA and carbon fiber, the dependence of deformations of the equivalent array with increasing load was established. The use of arched carbon fiber supports of various cross-sections can ensure the opening stability by reducing the intensity of stresses around its contour. On the basis of this study, a rational arched composite support of constant cross-section was proposed for the conditions of the «Dniprovska» mine. The obtained results indicate the need for further research, which will be considered in the author’s future works.